The social impact of partial edentations in a group of young adults - George Ion; Dan Cosmin Şerbănoiu; Mariana Păcurar; Rodica Luca (Amaltea Medical Publishing House, 2019)
Aim. To analyze the social impact of partial edentulism in young adults. Material and method. 300 patients, divided into two groups: group 1 (age 18-25) and group 2 (age 26-35), who presented at least one partial edentation completed a two-part questionnaire. The first part included socio-demographic data (age, sex, place of residency, education level) and the second part questions about how the presence of a possible front edentation could influence the individual's relationship with family, friends, couple life, or employment chances. The answers were analyzed according to the socio-demographic variables. Statistical processing was done with SPSS 13.0 for Windows. Results. For both groups statistically significant differences between the level of education and the employment opportunities were obtained (p <0.05). In group 1, the place of residency influenced relationships with friends and couple life, whereas in group 2 the most influenced were the couple's life and the chances of employment. Conclusions. In both age groups of young adults, the presence of a partial edentulism had a negative social impact on the quality of life.